Fulminant Essential Thrombocythemia Associated with Acquired Von Willebrand Syndrome and Bleeding Episodes in a 14-year-old Girl - Schneider, C.; Stutz-Grunder, E.; Lüer, S.; Keller, P.; Kremer Hovinga, J. A.; Ammann, R. A.; Karow, A. (Hämostaseologie, 2019)
Background Essential thrombocythemia is a chronic myeloproliferative neoplasm. It is extremely rare in children below 15 years of age with an estimated annual incidence of only 0.09 per million. Usually, clinical symptoms associated with essential thrombocythemia are mild or absent.Case Here, we present the case of a 14-year-old female patient fulminantly presenting with acute symptoms comprising visual impairment, palmar and plantar stabbing pain. Blood count revealed massive thrombocytosis of 2373 × 109/L. Bone marrow morphology showed elevated numbers of mature megakaryocytes. Von Willebrand factor activity/antigen ratio was significantly reduced compatible with an acquired Von Willebrand syndrome associated with high platelet counts. Molecular analyses for driver mutations of myeloproliferative neoplasms including JAK2V617F, CALR and MPL were negative. Acute therapy comprising hyperhydration and oxygen supply complemented by acetylsalicylic acid led to amelioration of symptoms. Medication with hydroxycarbamide maintained a significant reduction of platelet counts but had to be reduced or withheld several times due to neutropenia. Repeated bleeding episodes observed in the course were clearly associated with increases in platelet counts above 1200 × 109/L explained by acquired von Willebrand syndrome. Sixteen months after diagnosis, therapy was switched to pegylated interferon and platelet counts could be stabilized without significant side effects.
Keywords: essential thrombocythemia; myeloproliferative neoplasm; Von Willebrand syndrome